(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Youth unemployment is a significant problem in the Philippines, leading to economic insecurity, poverty, and social exclusion. Entrepreneurship has been used as a solution for developed countries to battle economic decline. Therefore, this study aims to argue that entrepreneurship is a viable solution for youth unemployment in Quezon City and propose an intervention program to support youth entrepreneurship. Both employed and unemployed respondents strongly agreed that entrepreneurship can promote economic growth, add additional income, generate employment opportunities, and improve the standard of living. The study also identified the challenges encountered by employed and unemployed individuals in entrepreneurship, such as a lack of financial capital, limited access to training and resources, and a lack of business experience. The study concludes that youth entrepreneurship can be a powerful tool for addressing youth unemployment in Quezon City. The proposed intervention program should focus on providing financial capital, training, and resources to young entrepreneurs, along with mentorship and networking opportunities. This program should be tailored to the specific needs of young adults in Quezon City and implemented in collaboration with government agencies, private organizations, and other stakeholders. Overall, this study provides valuable insights into the potential of youth entrepreneurship as a solution for unemployment and highlights the need for effective intervention programs to support young entrepreneurs.